Library technician course recognition: meeting the challenge of a distributed national education program - Hallam, Gill; Genoni, Paul (Australian Library and Information Association, 2009)
This paper looks at the challenges presented for the Australian Library and Information Association by its role as the professional association responsible for ensuring the quality of Australian library technician graduates. There is a particular focus on the issue of course recognition, where the Association?s role is complicated by the need to work alongside the national quality assurance processes that have been established by the relevant technical education authorities. The paper describes the history of course recognition in Australia; examines the relationship between course recognition and other quality measures; and describes the process the Association has undertaken recently to ensure appropriate professional scrutiny in a changing environment of accountability.